Early onset scoliosis: Can Best Practice Guidelines Be Provided in Europe? - Ilharreborde, Brice; Yazici, Muharrem; Yüksel, Selcen; Demir, Pervin; Helenius, Ilkka; EPOS Spine Study Group (SAGE Publications, 2026)
Background:
The goal of treatment in early onset scoliosis patients is to control the deformity while allowing chest and spinal growth. However, management, either conservative or surgical, remains controversial and require further clinical evidence. The aim of this study was to determine best practice guidelines for the management of early onset scoliosis patients in Europe.
Methods:
A Delphi approach was used among European experts to determine consensus in: (1) identification of progression risk factors, (2) clinical and radiographic evaluation, (3) conservative treatment, and (4) surgical management. Idiopathic and non-idiopathic groups were analyzed separately. Statements were only included in the final agreed consensus if at least 80% of respondents agreed with the statement.
Results:
A total of 22 pediatric orthopedic surgeons completed the first and second surveys, and 21 the third. Out of open-ended questions included in the initial Delphi, 75 statements for 59 multiple-choice questions in the idiopathic group and 47 statements for the 44 multiple-choice questions for the non-idiopathic group were formed for the second round. Of the total 122 statements, 50 (40.9%) reached consensus, and 72 did not. Among the 72 statements re-evaluated in Round 3, consensus was reached on 69 (96%).
Conclusion:
Early onset scoliosis represents a rare, heterogeneous, but life-threatening condition often associated with insufficient relevant evidence. Consensus is difficult to achieve (39.3% of the 122 statements), especially in the non-idiopathic group. However, 48 guidelines (33 for idiopathic and 15 for non-idiopathic) were provided by European experts to improve early onset scoliosis management.